Baksos Donor Darah dan Charity Pasar Murah Sembako: Wujud Kepedulian Lions Club Medan Angkasa dalam Mendukung Ketahanan Pangan dan Kesehatan Masyarakat di Kota Medan - Endy Juli Anto; Tim Lions Club Medan Angkasa; Steven Tjendra; Enney; Ronald T. H. Tambunan,; Frengky S. Manullang; Widjaya Taufik Tiji; Tengku M. Fauzi; Jadeny Sinatra; Juli Jamnasi; Jekson Martiar Siahaan (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
Voluntary blood donation and food assistance programs are two critical pillars of community service that address healthcare and socioeconomic disparities simultaneously. This community service activity, conducted by Lions Club Medan Angkasa (District 307 A2) in collaboration with PMI Kota Medan, aimed to increase blood stock availability while alleviating food insecurity among underprivileged communities in Medan. The combined event — "Baksos Donor Darah dan Charity Pasar Murah Sembako" — was held at the AXA Trust Agency Office, Jl. S. Mahameru No. 6 BC, Medan. Activities included voluntary blood collection, a subsidized staple food (sembako) market, and free health screening. A total of 120 voluntary donors registered; 108 successfully completed blood donation (90% success rate), yielding 108 blood bags (340cc each). Simultaneously, 200 staple food packages were distributed at subsidized prices, and free health checks were provided to 175 participants. Participant satisfaction surveys indicated 93% very satisfied. Building upon the success of the previous blood donation drive (Anto et al., 2025), this initiative further demonstrates the effectiveness of integrated community-based health and social welfare programs organized by Lions Club Medan Angkasa.